Love and Loss in Novel Wuthering Heights Through psychoanalisis Perspective - Devi Fitria; Novi Elisa (English Journal Antartika, 2025)
This study examines the theme of love and loss in Emily Brontë’s Wuthering Heights through a psychoanalytic and Gothic perspective. The novel portrays an extreme emotional relationship between Heathcliff and Catherine Earnshaw, in which love functions not merely as a romantic experience but as a psychological force that shapes identity, trauma, and emotional destruction. This research employs a qualitative descriptive method supported by thematic analysis to explore the construction of love, the causes of loss, and their psychological consequences for the characters. The data were collected through close reading of dialogues, narrative descriptions, and character interactions. The findings reveal that love in the novel is formed through childhood emotional bonding and identity fusion, while loss is generated by rigid social class structures, Catherine’s decision to marry Edgar Linton, and her death, which leads Heathcliff into a state of melancholia. This unresolved loss results in obsession, psychological suffering, and acts of revenge. Furthermore, Gothic elements reinforce the depiction of love that transcends death through spiritual and supernatural dimensions. The study concludes that Brontë represents love as an existential and destructive force, in which love and loss are inseparably intertwined and function as the central emotional conflict of the novel.